PROMOTING STARTUP BUSINESS’ SUCCESS IN UNIVERSITAS CIPUTRA SURABAYA: THE ROLE OF ENTREPRENEURSHIP EDUCATION - Soesanto, Carlyn; Hartono, Wendra; Hongdiyanto, Charly; Ongkowijoyo, Gracia (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Entrepreneurship is one of the ways to decrease the unemployment rate and promote economic growth. Entrepreneurial character can be taught through entrepreneurship education, which also help new entrepreneurs to minimize failure rate when starting a business. Universitas Ciputra Surabaya (UCS) is considered as the pioneer of entrepreneurial university in Indonesia and has an entrepreneurship course series called E-Wednesday. This university encourages students to have entrepreneurial spirits. The purpose of this study is to explore the role of entrepreneurship course in UCS toward startup business’ success. Semi-structured interview, documentation, and secondary data were used to collect data. Purposive sampling was used to select informants. The result of this study indicates that E-Wednesday gives positive impact and contributes to students startup business’ success. Students can implement the theories learned when creating real business projects. The entrepreneurship course has important roles such as to provide mentoring, facility, networking, and motivation for students. Specifically, UCS’s E-Wednesday provides students not only business lecturers, but also real entrepreneurs as facilitators. Exhibition, workshop, bazaar, and business incubators are the facilities provided by E-Wednesday to help students develop their businesses. Nonetheless, there are still some improvements to be made for the betterment of E- Wednesday. Keywords: Entrepreneurship Course, Startup Business’ Success, Qualitative Method